Edukasi terhadap Obat, Makanan, Kosmetik, dan Lingkungan yang Terkontaminasi Bakteri dan Jamur - Artha Yuliana Sianipar; Grace Anastasia br Ginting; Peri Peri; Axeldykes Yergal Nainggolan; Chatrin Sasya Christiawan Damanik; Desi Olifya Simanungkalit; Eli Putri Simanjuntak; Friskila Magdalena Simatupang; Jennifer Audi Inesza Silitonga; Keysia Aurel Sinaga; Laudia Cintia; Nalatari Simamora (Lembaga Pengembangan Kinerja Dosen, 2026)
The microbiological safety of drugs, food, cosmetics, and environmental samples is a crucial factor affecting public health. This study aimed to evaluate contamination levels using the Total Plate Count (TPC/ALT) method and to identify potential pathogenic bacteria. A quantitative approach was conducted using the pour plate technique, where samples were serially diluted, inoculated on Plate Count Agar (PCA), and incubated at 35–37°C for 24–48 hours. The results showed significant variations in bacterial load across samples. Liquid cosmetic products such as sunscreen and foundation exhibited high contamination levels ranging from 1.23×10⁵ to 3.2×10⁶ CFU/g, exceeding the regulatory limit of 10³ CFU/g. Pathogenic bacteria including Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli were detected, indicating contamination from environmental exposure, poor hygiene practices, and cross-contact during usage. In environmental samples, extremely high microbial counts indicated active biological recovery. These findings demonstrate that many products fail to meet microbiological safety standards after use. Therefore, strict hygiene control, effective preservative systems, and proper storage practices are essential to minimize contamination risks and ensure consumer safety.